Sustainable Lake Management Framework for Performance Monitoring and Quality Assessment - Shafee, Farah Amira Ahmad; Shafiq, Nasir; Farhan, Syed Ahmad; Adebanjo, Abiola; Razak, Siti Nooriza Abd; Kumar, Vicky (Migration Letters, 2024)
Lake ecology and regional development require a sustainable lake management framework. Blue space was examined for its health and city sustainability benefits. Lake deterioration causes, levels, benefits, and degrees were analysed to develop a strategic framework. The proposed framework uses structural equation modelling (SEM) to analyse four categories. These categories address lake issues like management support, lake improvement, funding and lake visitor benefits. Path coefficients support two hypotheses; however, one hypothesis was not supported due to p-value of < 0.05. The most significant path T=3.262 was between concern (H.C) and benefits (B), followed by 2.147 for H.C and S, all with a p-value of 0.000. For lakes’ sustainable management, the study found lakes development contribution is paramount. The lake encourages access to nearby facilities and raises awareness of residential development costs. Knowing regional and local lake changes enables sustainable lake management decisions which suit lake needs and surroundings.